Bibliometric Analysis on Metacognition and Self-Regulation Using Biblioshiny Software - Devaki, V.; Ramganesh, E.; Amutha, S. (Indian Journal of Information Sources and Services, 2024)
This study aims to conduct a systematic review of Metacognition and Self-Regulation [MSR], with a focus on current trends and contributions. Initial analysis involves Elsevier’s Scopus database spanning from 1988 to 2023, with refined search parameters including source type, language, and document type. Later, bibliometric analysis was conducted using Biblioshiny software, exploring various factors derived from the Scopus core collection database [N=428] on the search title MSR. The results highlight trending topics such as cognition, engineering design, memory, and engineering education. Notably, the most prevalent co-occurrence network involves metacognition, student, and self-regulated learning. Analysis of the most influential authors, affiliated institutes, citation analysis, and source production was discussed. The objective of this paper is to assist researchers and scholars in understanding and analyzing contemporary trends in MSR, as well as suggesting further empirical research to explore additional principles related to metacognition and self-regulated learning.